To jog or to stride: A comparison between two standardised running tests to monitor neuromuscular status in team sport athletes - Leduc, C.; Sawczuk, T.; Russell, S.; Lacome, M.; Garrett, J. M. (Journal of Sports Sciences, 2024)
This study investigated: 1) monitoring post-match neuromuscular fatigue (NMF) status in rugby union players using two submaximal running tests (SRT); and 2) the sensitivity of each SRT to locomotor variables obtained during match-play. Twenty-three male rugby players (age: 21.0 ± 1.3 years; height: 185.2 ± 6.1 cm; body mass; 97.3 ± 10.3 kg) were monitored across one season (n = 71 player-match and 159 fatigue-players-testing observations). Two different SRTs (SRT-jog [5-minute shuttle run protocol] and SRT-stride [a repeat stride effort protocol]) were used to characterise post-match NMF, with measures taken two days prior to match day (baseline), on MD + 1, and MD + 2. Linear mixed models (±90% CIs) were used to explore differences between measures and match-play locomotor variables. SRT-jog presented a meaningful increase following MD + 1 (ES: 0.63 [0.37 to 0.89]). SRT-Stride showed small increases at MD + 1 (ES: 0.24 [0.02 to 0.49]) and MD + 2 (ES: 0.33 [0.07 to 0.59]) suggesting a potential impairment in running mechanics. SRT-stride was significantly associated with total distance (ES: 0.41 [-0.01 to 0.83]) and collisions (ES: 0.58 [0.18 to 0.99]). While both tests presented small to moderate changes post-match, only the SRT-stride was related to match locomotor variables. Therefore, the SRT-stride may be a more sensitive monitoring tool for monitoring NMF in rugby union players.